Impact of Dialysis on the Dyadic Relationship Between Male Patients and Their Female Partners. (February 2020) - Moore, Currie; Skevington, Suzanne; Wearden, Alison; Mitra, Sandip
The objective of this study was to explore the impact of three early phases of renal dialysis, namely pre-dialysis, starting dialysis, and establishing dialysis, on dyadic relationships. Twenty UK-based dyads (20 male patients and their female partners) participated in semi-structured interviews and discussed the effects of dialysis on themselves and their relationship. Dyadic thematic analysis, facilitated by dyadic-level charting, integrated participants' experiences and enabled identification of patterns across dyads. We found that dialysis had positive and negative influences on identity, social relationships, and mental health, forming the themes: Prioritizing the Patient, Carrying the Burden, and Changing Identities. The final theme, Managing the Relationship, described how dyads prevented dialysis from negatively impacting their relationship. Dyadic-level charting provided a systematic examination of individual and dyadic experiences. These findings indicate that access to informational and support services for dyads as they prepare to start dialysis may minimize negative effects on their relationship.